Analisis Daya Saing Ekspor Biji Kopi Indonesia dan Vietnam di Pasar Amerika Serikat - Shanaya Nafsani (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Coffee is one of the products from Indonesia's leading agricultural sector. Coffee participates greatly in Indonesia's export activities, especially to the United States. But so is Vietnam. The purpose of this study was to analyze the competitiveness of Indonesian and Vietnamese coffee beans in the United States market as the largest importing country for Indonesian coffee beans. The research method used is panel data analysis taken from secondary data. The analysis uses two methods, namely Revealed Comparative Advantage (RCA) analysis and also Constant Market Share Analysis (CMSA). The results show that Indonesia and Vietnam have a comparative advantage in several types of coffee commodities. In general, the results from the CMSA also show that the competitiveness of Indonesian coffee is positive, indicating that Indonesia is able to take a share of the coffee bean market in the 2016-2018 period.